Successful Use of Leukocyte Platelet-Rich Fibrin in the Healing of Sinus Membrane Perforation: A Case Report - Santos Pinto, Gustavo Da Col dos [UNESP]; Pigossi, Suzane Cristina; Pessoa, Tercio [UNESP]; Nicoli, Lelis Gustavo [UNESP]; Souza Bezerra Araujo, Raphael Ferreira de [UNESP]; Marcantonio, Claudio; Marcantonio, Elcio [UNESP] (Lippincott Williams & Wilkins, 2018)
Purpose: The aim of this case report was to demonstrate the repair of a large sinus membrane perforation related to a sinus floor augmentation procedure, using leukocyte platelet-rich fibrin (L-PRF), for subsequent rehabilitation of a partially edentulous patient. Materials and Methods: The patient presented the absence of teeth numbers 18, 17, and 16, associated with insufficient bone height because of the maxillary sinus pneumatization. A maxillary inlay bone graft was proposed, however, during the sinus floor augmentation procedure, a large portion of the sinus membrane was ruptured. To avoid interruption of the surgical procedure, membrane mending was proposed using L-PRF and collagen membranes. Results: After 8 months, 2 external hexagon connection dental implants were placed in the 16 and 17 teeth regions, and a screw-retained implant-supported prosthesis was installed. Conclusion: The use of L-PRF associated with collagen membrane was efficient for the sealing of the sinus membrane perforation and enabled bone formation for subsequent implant installation.
Keywords: dental implants; bone regeneration; bone substitutes; leukocyte platelet-rich fibrin (L-PRF); sinus membrane perforation; sinus floor augmentation